Cyanide Binding to [FeFe]‐Hydrogenase Stabilizes the Alternative Configuration of the Proton Transfer Pathway. Issue 7 (10th January 2023) - Duan, Jifu; Hemschemeier, Anja; Burr, David J.; Stripp, Sven T.; Hofmann, Eckhard; Happe, Thomas
Abstract: Hydrogenases are H2 converting enzymes that harbor catalytic cofactors in which iron (Fe) ions are coordinated by biologically unusual carbon monoxide (CO) and cyanide (CN − ) ligands. Extrinsic CO and CN −, however, inhibit hydrogenases. The mechanism by which CN − binds to [FeFe]‐hydrogenases is not known. Here, we obtained crystal structures of the CN − ‐treated [FeFe]‐hydrogenase CpI from Clostridium pasteurianum . The high resolution of 1.39 Å allowed us to distinguish intrinsic CN − and CO ligands and to show that extrinsic CN − binds to the open coordination site of the cofactor where CO is known to bind. In contrast to other inhibitors, CN − treated crystals show conformational changes of conserved residues within the proton transfer pathway which could allow a direct proton transfer between E279 and S319. This configuration has been proposed to be vital for efficient proton transfer, but has never been observed structurally. Abstract : [FeFe]‐hydrogenases are highly efficient H2 biocatalysts that employ intrinsic CN − ligands. Here, extrinsic CN − is shown to bind at the open coordination site of the catalytic center. Additionally, new conformations within the proton transfer pathway that are complementary to those in the oxidized state Hox are observed, providing a structural basis for understanding the molecular mechanisms of rapid proton shuttling within enzymes.